2016
DOI: 10.1523/jneurosci.3575-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Microglia for the Maintenance of Synaptic Function and Integrity in the Mature Retina

Abstract: Microglia, the principal resident immune cell of the CNS, exert significant influence on neurons during development and in pathological situations. However, if and how microglia contribute to normal neuronal function in the mature uninjured CNS is not well understood. We used the model of the adult mouse retina, a part of the CNS amenable to structural and functional analysis, to investigate the constitutive role of microglia by depleting microglia from the retina in a sustained manner using genetic methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
157
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 61 publications
12
157
1
1
Order By: Relevance
“…These cells represent either PLX-resistant, nondepleted microglia or infiltrated macrophages. PLX5622-induced retinal microglia deficiency was also more pronounced compared with a genetic approach, which showed only nearcomplete depletion and some long-term repopulation (Wang et al, 2016). Treatment times might possibly be reducible, but we found that 1 week of PLX5622 diet was insufficient to achieve complete depletion, similar to previous studies in brain .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These cells represent either PLX-resistant, nondepleted microglia or infiltrated macrophages. PLX5622-induced retinal microglia deficiency was also more pronounced compared with a genetic approach, which showed only nearcomplete depletion and some long-term repopulation (Wang et al, 2016). Treatment times might possibly be reducible, but we found that 1 week of PLX5622 diet was insufficient to achieve complete depletion, similar to previous studies in brain .…”
Section: Discussionsupporting
confidence: 85%
“…As described previously, Iba1-positive cells were detected in the GCL, IPL, and OPL (Fig. 1A-C) (Wang et al, 2016) and the entire optic nerves (Fig. 1D) of untreated mice.…”
Section: Efficient Depletion Of Microglia In Retinae and Optic Nervessupporting
confidence: 80%
See 1 more Smart Citation
“…Microglial cells are implicated in the maintenance of synaptic integrity [62] and, in fact, could promote learning-dependent synaptic formation [41]. In addition, microglia is involved in Abeta phagocytosis [27, 64, 65], senile plaque compaction, and limitation of Abeta toxicity [7, 66].…”
Section: Discussionmentioning
confidence: 99%
“…The short-term effects of such drastic approaches appear to be subtle, expressed as mild cognitive impairments (Parkhurst et al, 2013) or with no behavioral effects at all (Elmore et al, 2014). Ablation of microglia does not induce neuronal loss, but longer-term ablation can cause synaptic degradation (Parkhurst et al, 2013;Spangenberg et al, 2016;Wang et al, 2016). Intriguingly, in mouse models of Alzheimer's disease with its hallmark microglial activation and proliferation, the effects of microglial ablation are beneficial (Hong et al, 2016;Olmos-Alonso et al, 2016;Spangenberg et al, 2016).…”
Section: The Brain-resident Immune Systemmentioning
confidence: 99%